Rhabdomyosarcoma of the maxillary gingiva - Mina Motallebnejad; Pouyan Aminishakib; Samira Derakhshan; Abbas Karimi (Wolters Kluwer Medknow Publications, 2018)
Rhabdomyosarcoma is a malignant skeletal muscle neoplasm. The tumor is much more common in children, and the most frequent site is head and neck region. Since this tumor is less frequent than other neoplasms in oral cavity, the clinicians sometimes ignore it, working the patients up. Rhabdomyosarcoma is a high-grade malignancy with poor prognosis. Considering the aggressive behavior and various clinical or histopathologic presentations of the tumor, early diagnosis has a significant impact on the treatment outcome and prognosis of the patients. We highlight the importance of combining the clinical, radiographic, and histopathologic examination to obtain a definitive diagnosis in sarcomas of the head and neck region, especially rhabdomyosarcoma. A case of rhabdomyosarcoma of the maxillary gingiva is presented in a 32-year-old woman in which the primary incisional biopsy was erroneously interpreted as an inflammatory process and consequently, the accurate diagnosis postponed for about 10 months.